(3OhQ GdHJQhd aj Jehjd GdJfejI GdGbJUGOjI aj HdOGf GdTQb GdChSW (B/ s - (3jSQi eMeO CHh GdYdGs; (3YGWa UObjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B- (3LGeYI GdbGgQI,s, 1981)
(3jJVef gPG GdHMK Edi bSejf QFjSjjf(B: (3GdChd (B: (3OQGSI GdfaW GdYQHj hGdJfejI GdGbJUGOjI, hjJef Ydi HGHjf (B1- (3CgejI GdfaW GdYQHj ef MjK NUGFUg hOhQI ceUOQ QFjSj ddWGbI aj GdYGde, (B2- (3HMK JMOjO eaghe GdJfejI GdGbJUGOjI GdKGfj (B: (3OQGSI hHMK OhQ GdfaW aj Jehjd GdJfejI ddHdOGf GdYQHjI HefWbI GdTQb GdChSW hcaGAI GSJNOGe GdEjQGOGJ GdHJQhdjI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdeGdjI GdYGeI hGdJTQjY GdVQjHj (B1981.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B400-445. s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJfejI GdGbJUGOjIs; (3GdGSJjQGO hGdJUOjQs; (3TQcGJ GdGSJKeGQ GdYQHjIs; (3GdQShe GdLeQcjIs; (3GdHJQhds; (3GdJYGhf GdYQHjs; (3GdejRGf GdJLGQjs; (3GdJLGQI GdNGQLjIs; (3GdfXGe GdeUQajs; (3GdGShGb GdeGdjI GdOhdjIs; (3GdYQV hGdWdHs; (3GdJVNe GdeGdjs; (3GdONd Gdbhej s; (3GdJNda GdUfGYjs; (3GdWGbI GdfhhjIs; (3GSJgdGc GdWGbIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdeGdjI GdYGeIs